Investigating Blended Learning Impact on Students Vocabulary Achievement - Minkhatun Nakhriyah; Hanafi Wibowo (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This study attempts to investigate the effect of the blended learning approach on student’s vocabulary achievement. The methodology of this study used Quasi experiment method and randomized post-test only control group design. A sample were 60 grade ten students of SMK Bina Insan Kamil, Bekasi where divided two experiments and control group which the experiment tough by a blended learning approach, and control group learned the same vocabularies trough conventional way. Analyze of the instrument in this study in items of validity, reliability, difficulty index and discrimination power used SPSS and analyze the data used T-test to know whether the alternative hypothesis (Ha) was accepted or rejected. The result of this study showed that there was a significant effect of blended learning approach on student’s vocabulary achievement. The significant (Sig) score of 0.003 is smaller than (<) 0.05. So that this study has a significant effect of blended learning on student’s vocabulary achievement. Moreover, the approach of blended learning enhances their motivation to learn vocabularies in the learning process.